Customized development interventions for the ultra poor: Preliminary change assessments of health and health-seeking behaviour (CFPR/TUP 2002 to 2004) - Ahmed, Syed Masud; Rana, AKM Masud (BRAC Research and Evaluation Division and Aga Khan Foundation Canada, 2022)
The paper sets out to explore the achievements of civil society in the area of poverty reduction. The focus is mainly on three domains (1) Advocacy; (2) Policy Change, and (3) Service Delivery. Three case studies illustrate how poverty can be addressed at various levels and through different approaches: (1) Shack Dwellers International (SDI) operating internationally to advocate for the urban poor’s rights; (2) civil society organizations participating in the formulation of PRSPs to call for pro-poor policy reforms at the national level, and finally (3) the example of BRAC (formerly the Bangladesh Rural Advancement Committee) providing services to the poorest at the grassroots level. Drawing on these case studies, the paper explains the keys to success and reasons for the failure of civil society organizations in tackling poverty reduction effectively. It concludes by pointing out the challenges faced by civil society in the area of poverty reduction and presents recommendations on ‘what is still missing’ for civil society to play a more effective role in poverty reduction.